Sex- and Age-Related Differences in Bone Microarchitecture in Men Relative to Women Assessed by High-Resolution Peripheral Quantitative Computed Tomography - Shreyasee Amin; Sundeep Khosla (Journal of Osteoporosis)
The trabecular and cortical compartments of bone each contributes to bone strength. Until recently, assessment of trabecular and cortical microstructure has required a bone biopsy. Now, trabecular and cortical microstructure of peripheral bone sites can be determined noninvasively using high-resolution peripheral quantitative computed tomography (HR-pQCT). Studies that have used HR-pQCT to evaluate cohorts of both men and women have provided novel insights into the changes in bone microarchitecture that occur with age between the sexes, which may help to explain the lower fracture incidence in older men relative to women. This review will highlight observations from these studies on both the sex- and age-related differences in trabecular and cortical microstructure that may underlie the differences in bone strength, and thereby fracture risk, between men and women.